Critical thinking and its importance in education: some reflections - Uribe Enciso, Olga Lucía; Uribe Enciso, Diana Sofía; Vargas Daza, María Del Pilar (Rastros Rostros, 2017)
Purpose: This article reviews some conceptions of critical thinking and highlights its importance for education. Description: First, it presents some philosophical and psychological approaches to critical thinking and their influence in international and national educational policies as a means of fostering active citizenship and in turn sustainable development. Second, it highlights the relation between critical thinking and Content and Language Integrated Learning. Third, the authors of this article insist on the vital role teachers have on developing critical thinking. Point of view: The concept of critical thinking has been approached by different academicians through history. However they may differ, they all have in common features such as intellectual discipline, integrity, freedom, citizenship, creativity and empathy. Therefore, critical thinking development must be inherent in education as societies need citizens who facilitate their progress. An example of how critical thinking can be developed in education is illustrated through the implementation of CLIL in language classes. Conclusion: Having in mind that students spend a lot of time in school, teachers are called to help family to develop our students’ critical thinking skills during their regular teaching practices.